RESISTENSI BIOKIMIA BIBIT JABON PUTIH (Anthocephalus cadamba (Roxb.) Miq.) TERHADAP Botryodiplodia theobromae Pat. PENYEBAB PENYAKIT MATI PUCUK - Lola Adres Yanti; Ahmad Ahmad Ahmad; Nurul Khumaida (Jurnal Agrotek Lestari, 2018)
Dieback disease on white jabon seedlings is caused by Botryodiplodia theobromaedecreased seedlings quality, economic benefits of nurseries, and seedling death. There is no research for resistance of white jabon to pathogen attacked. This research aimed to study the biochemical resistance of white jabon to B. theobromae attacked. The biochemical resistance was done with studying the chemical compound of white jabon seedlings’ stem used phytochemistry analysis. The results showed that the biochemical resistance before pathogen attacked for white jabon seedlings were found alkaloids, flavonoid, phenol hydroquinone,tannin, saponins, and steroids. After pathogen attacked, the biochemical resistance of white jabon seedlings had the increase in the content of flavonoid, tannin, saponins, triterpenoid and steroids. Keywords: Botryodiplodia theobromae, stem infection methods, the increase of secondary metabolite content, white jabon seedling